A Novel Polysaccharide From Chuanminshen violaceum and Its Protective Effect Against Myocardial Injury - He, Peng; Zhang, Mi; Zhao, Meng; Zhang, Mengyao; Ma, Benxu; Lv, Hongyu; Han, Yantao; Wu, Dingtao; Zhong, Zhangfeng; Zhao, Wenwen (Frontiers in Nutrition, 2022)
We isolated and purified a novel polysaccharide from the root of Chuanminshen violaceum namely CVP and confirmed its structure and molecular weight. Furthermore, in vivo experiment, CVP’ protective effect against myocardial ischemia-reperfusion (I/R) injury in mice was evidenced by significantly reducing I/R-induced myocardial infarction size, decreasing the secretion of heart damage biomarkers as well as improving cardiac function. Then, myocardial anoxia/reoxygenation (A/R) injury model was established to mimic reperfusion injury. Noticeably, ferroptosis was the major death manner for A/R-damaged H9c2. Moreover, CVP significantly decreased intracellular Fe2+ level, reduced GPX4 expression as well as suppressed lipid peroxidation to confront A/R injury. In conclusion, CVP, with a clear structure, significantly improves I/R injury by inhibiting ferroptosis.